2013
DOI: 10.1021/la4003252
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoluminescence by Tyrosine-Containing Bolaamphiphile Self-Assembly

Abstract: Photoluminescent spherical nanostructures were prepared through the self-assembly of a tyrosine-containing bolaamphiphilic molecule, and their antenna effect was examined. The photoluminescent spherical nanostructures were simply prepared by self-assembly of bolaamphiphile molecules in an aqueous solution in which water-soluble photosensitizers and lanthanide ions were dissolved. The photosensitizers and lanthanide cations were incorporated with the phenol group and the carboxyl end of the tyrosine moiety, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…20 Synthesis and self-assembly of the tyrosyl bolaamphiphile molecule (Tyr-C7) were performed according to previously reported protocols. 11 Briefly, the Tyr-C7 molecule was synthesized by conjugating tyrosine benzylester with azelaic acid through a carbodiimide conjugation. The photoluminescent self- 25 assembly suspension was produced by dissolving the prepared tyrosyl bolaamphiphile at a concentration of 2 mg/ml in an aqueous solution containing photosensitizer and lanthanide ion (Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Synthesis and self-assembly of the tyrosyl bolaamphiphile molecule (Tyr-C7) were performed according to previously reported protocols. 11 Briefly, the Tyr-C7 molecule was synthesized by conjugating tyrosine benzylester with azelaic acid through a carbodiimide conjugation. The photoluminescent self- 25 assembly suspension was produced by dissolving the prepared tyrosyl bolaamphiphile at a concentration of 2 mg/ml in an aqueous solution containing photosensitizer and lanthanide ion (Fig.…”
Section: Figmentioning
confidence: 99%
“…S1), which can be used as a photoluminescent probe. 11 Since these photoluminescent probes are easily prepared and dispersed in water, and have surface-exposed tyrosine phenolic groups, they are well suited for the evaluation of molecular interactions through fluorescence quenching. 60 In the present work, the effect of molecular structures of nitroaromatic compounds on photoluminescence quenching was investigated using a photoluminescent bolaamphiphile selfassembly as a photoluminescent probe.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the tyrosine–photosensitizer conjugates, a tyrosine‐rich solid matrix is a promising platform for the preparation of a PSII mimetic system. We recently reported that tyrosyl bolaamphiphile assembly (TyrBA) could yield a proteinaceous nanoscale solid matrix with the exposure of densely packed tyrosine phenol groups on the surface . TyrBA displayed biochemical activities of the tyrosine phenol groups and exhibited outstanding mechanical strength that originated from intermolecular interactions, such as hydrophobic interactions and hydrogen bonds.…”
Section: Introductionmentioning
confidence: 98%
“…We recently reported that tyrosyl bolaamphiphile assembly (TyrBA) could yield ap roteinaceous nanoscale solid matrixw ith the exposure of densely packed tyrosine phenol groups on the surface. [17,18] TyrBA displayed bio-…”
Section: Introductionmentioning
confidence: 99%
“…16 Also, the selfassembly technique had been found to be quite useful for improved device performances. For example, improvements in RS characteristics and enhancements in photoluminescence properties using self-assembled gold−peptide nanofiber nanostructures 19 and spherical bolaamphiphiles 20 were recently reported.…”
Section: ■ Introductionmentioning
confidence: 99%